A study to identify various bacteria in conjunctiva among the diabetic and non-diabetic individuals - Sarma, S Srinivasa; Dr. T Jaya Chandra (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Diabetes mellitus is a multi-factorial disease that can affect all ocular structures. With this a study was conducted to isolate and identify the organisms from the conjunctival flora of normal and diabetic population. Materials and methods: Study was conducted in department of Microbiology, GSL Medical College, Rajahmundry. Surgically removed cataract lens were collected from diabetic and nondiabetic individuals in sterile nutrient broth and transported immediately to Microbiology laboratory for culture and sensitivity testing, processed and identified as per the standard protocol. Isolates were subjected to antibiotic sensitivity analysis using Kirby Bauer disc diffusion method. Results: During the study period, 30 samples each were collected from diabetic and non-diabetic individuals who underwent cataract. Culture positive results were more (76.6%) in diabetic patients; Isolate wise, gram positive cocci were 53.3%, 57%, gram positive bacilli (GPB) were 26.6% each and gram-negative bacilli (GNB) were 3.3%, 19.8% respectively in non-diabetic and diabetic patients. statistically the difference was not significant. And the isolates were increased with age. Conclusion: The prevalence of isolation was almost similar among the non-diabetics and diabetic population. In both groups, rate of isolation was increased with age and no significant drug resistance was observed.